Kinetic energy of M2 tide in the Makassar Strait. Issue 1 (May 2021) - Pelawi, E S B S; Ikhwan, M; Haditiar, Y; Wafdan, R; Muhammad, M; Rizal, S
Abstract: The Makassar Strait (MS) is the main passage through the Pacific to Indonesian waters, which divides the islands of Kalimantan and Sulawesi. These waters are rich with natural resources. The research objective was to determine the energy produced by the M2 tides in the Makassar Strait. Ocean currents and energy are analyzed from the output of a two-dimensional numerical model. The results showed that the tidal flow velocity in the Makassar Strait was above 1 m/s, especially in Balikpapan (1.1975 m/s, ) Mamuju (1.3379 m/s), and Pantoloan/Palu (1.2728 m/s). While the power or tidal current energy in Balikpapan is 3, 6238 × 10 4 kWatt, Mamuju is 2, 0215 × 10 5 kWatt, and Pantoloan/Palu is 7, 4006 × 10 5 kWatt. The tidal energy is intense in Pantoloan/Palu compared to other stations.